Aerosolized Antibiotics. Issue 5 (September 2017) - Dugernier, Jonathan; Reychler, Gregory; Dubus, Jean-Christophe; Ehrmann, Stephan
Abstract : Aerosolized antibiotics potentially enable delivery of drugs directly at the site of lung infection with limited systemic side effects. Progress in understanding determinants of pharmacokinetics and drug deposition in the lung enable delivery of high antibiotic concentrations in the lung. The present review summarizes experimental and clinical pharmacokinetic and scintigraphic deposition studies evaluating aerosolized antibiotics. Practical implementation of different aerosolization devices is reviewed for delivery to patients breathing spontaneously or undergoing mechanical ventilation. Current clinical indications among patients suffering from cystic fibrosis, bronchiectasis, and ventilator-associated pneumonia are presented as well as further perspectives for development for this appealing modality of antibiotic therapy.